Venom serine proteinase homolog of the ectoparasitoid Scleroderma guani impairs host phenoloxidase cascade. (August 2020) - Wu, Chao-Yan; Huang, Jing-Mei; Zhao, You-Jie; Xu, Zhi-Wen; Zhu, Jia-Ying
Abstract: The ant-like bethylid ectoparasitoid Scleroderma guani (Hymenoptera: Bethylidae) envenomates host to suppress immune response. Yet, the roles of its venom in inhibiting melanization of the host hemolymph have not been fully characterized. Here, we demonstrated that S. guani envenomation induced strong inhibition of melanization of the hemolymph from Tenebrio molitor (Coleoptera: Tenebrionidae), permitting the successful development of parasitoid offspring. To reveal venom component associated with such function, a serine proteinase homolog (SguaSPH) rich in the venom of S. guani was characterized. It was found that one of the catalytic triad residues for serine proteinase is absent in the amino acid sequence of SguaSPH. This venom component was abundantly expressed in venom apparatus and adult stages. By enzymatic assays, SguaSPH displayed low trypsin and no chymotrypsin activity, and was able to inhibit phenoloxidase activity in the hemolymph of Ostrinia furnacalis (Lepidoptera: Crambidae). The findings suggest that SguaSPH is essential for interfering with hemolymph melanization of S. guani envenomated host via phenoloxidase cascade disruption. Graphical abstract: Image 1 Highlights: Scleroderma guani envenomation suppressed melanization of the host hemolymph. Serine proteinase homolog gene was abundantly expressed in venom apparatus. Venom serine proteinase homolog has low trypsin and no chymotrypsin activity. Melanization of the host hemolymph was inhibited by venom serine proteinase homolog.